VACCINE PROPHYLACTICS’ OF INFLUENZA AND PNEUMOCOCCAL INFECTION IN SICKLY CHILDREN - Isayeva, R.F. (World of Medicine and Biology, 2013)
Treatment and prevention of respiratory tract infections one of the global problems in the nosology of infectious pathology. To assess the state of the cells and humoral immunity of recurrent respiratory tract infection of the children before and after combined scheme of immunization conducted vaccine "Pneumo-23" and the influenza vaccine. Considering the totality of the above, we can say with confidence that the concomitant vaccination influenza vaccine "Influvak" and the vaccine "Pneumo-23" is an effective means of reducing respiratory pathology in RTI, to facilitate the clinical course of disease, and significantly improves the immunological protection of sickly children .Thus in the fight against respiratory viral diseases in the RTI, this method of immunization has proved highly effective, evidence-based and clinically proven.